(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study explored the forensic accounting skills needed by internal auditors for effective auditing in public universities. In order to carry out this study, two research questions was raised and two null hypotheses were tested at 0.05 level of significance. The study adopted descriptive survey research design. The entire population of 137 internal auditors in all the seven federal universities and thirteen state universities in South-South Nigeria was used without sampling. A structured questionnaire containing 19 items, which was validated by three experts was used for data collection. Cronbach alpha formula was used to determine the internal consistency of the questionnaire which yielded an overall reliability co-efficient of 0.83. The researchers administered the instrument with the help of five research assistants to the respondents. Mean and standard deviation were used to answer the research questions and determine the homogeneity or otherwise of the respondents while t-test was used to test the null hypotheses. Findings of the study revealed that communication skills and analytical procedure skills are greatly needed by internal auditors for effective auditing in public universities in South-South Nigeria. Internal auditors did not differ significantly in their mean ratings on communication skills and analytical procedure skills needed for effective auditing in public universities in South-South Nigeria based on institutional ownership. The study concluded that communication skills and analytical procedure skills are highly needed by internal auditors for effective auditing in public universities in South-South Nigeria. It was recommended among others that internal auditors in financial audit departments of public universities in South-South Nigeria should undergo professional training and development programmes on communication skills in order to meet the expectations of their profession.